Analiza zawartości informacyjnej dywidend na Giełdzie Papierów Wartościowych w Warszawie - Orzechowski, Arkadiusz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The article analyzes efficiency of the Warsaw Stock Exchange with respectto dividends’ payments. The article presents possible causes of anomaly relatedto dividends, reviews the English language literature of the field and finally presents the results of empirical studies related to companies listed on the Warsaw StockExchange. The results indicate that it is possible to construct investment strategysystematically generating financial benefits which proves that the Polish capitalmarket is ineffective.